The Effect of Education Based on the Family-oriented Empowerment Model on Self-care Behaviors of Patients with Type 2 Diabetes Referred to Rural Health Centers in Neka - Sareh Shakerian; Homeira Amini (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Self-care and patients education is the core of diabetes care and control. Family as the most fundamental pillar of society is responsible for the provision of proper and appropriate health care. The current study aimed to investigate the family-oriented empowerment model on self-care behaviors of patients with Type 2 diabetes in Neka. Methods: This quasi-experimental study was conducted on patients with diabetes mellitus referring to comprehensive rural health centers in Naka. They were randomly assigned into two groups of intervention and control. The intervention group received training for three months. Data collection instrument included  Summary of Diabetes Self Care Activities(SCSCA) questionnaire consisting of two parts, namely demographic characteristics and dimensions of self-care activities(including diet, random blood glucose, physical activity, foot care, fasting blood sugar). The obtained data were analyzed in SPSS software( version 24). Results: Based on the results of the study,  there was a significant difference in the mean scores before and after the intervention in terms of blood sugar, dietary control, and self-care behaviors (P <0.05). However, the mean scores before and after intervention in foot care, insulin consumption, and Physical activity was not significantly different (P> 0.05). Conclusion: The results were indicative of the impact of family-Oriented empowerment education on most self-care behaviors of patients with type 2 diabetes.